Governing Role of Trade Digitalization in Global Supply Chain Finance, Negotiation and SMEs Performance - Sudawan Somjai; Saroge Vasuvanich; Khomsan Laosillapacharoen; Boonsri Suteerachai (International Journal of Supply Chain Management, 2019)
Thailand is witnessing a significant growth in Small and Medium Enterprises (SMEs) especially in manufacturing sector. Yet, their survival is totally based on their performance that can only be ensured through good supply chain practices. Supply chain finance and negotiation are some relevant practices that can have their say in improved SMEs performance but trade digitization is another important factor to be considered prior to conclude results. This study has analyzed the role of supply chain finance and negotiation in improving SMEs performance in moderating role of trade digitization. Around 35 SMEs of Thailand’s manufacturing sector and their employees dealing in production department were surveyed through questionnaire and data was then analyzed through structural equation modeling. Results have indicated that both supply chain negotiation and supply chain finance have significant impact on SMEs performance while trade digitalization significantly moderate both the relationships. Study has originality due to moderating role of trade digitization between supply chain negotiation and SMEs performance. This research has its implications for SMEs operating in Thailand in any sector along with policy framework for government too.